The Role of Education Technology in Mathematic of Third Grade Students in MI Ma’arif Pademonegoro Sukodono - Nurdyansyah Nurdyansyah; Pandi Rais; Qorirotul Aini (Universitas Muhammadiyah Sidoarjo, 2017)
This research aimed at finding out the important rule of technology, and supporting and inhibiting factors in math among the third grade students of MI Ma’arif Pademonegoro. This research was field research by the design qualitative description study. The data collections were interview, observation, documentation, and analysis by using triangulation analysis. The tools of technology that often used by the teachers in Mathsss of third grade students in MI M’arif Pademonegoro were 1) laptop, 2) power point slide, 3) LCD. There were some supporting tools of education as: the preparation of teachers in learning process and technology tools. On the other hand, there were some obstacles in application such as the monotonous of teaching styles and passive students.